SEPTEMBER 1992 ACTIVITY REPORT (Tufts Archival Research Center, 2007)
Letter from Wes Lane to Jim Savarese regarding the September 1992 Activity Report. Describes the author's efforts to do research on smoker's rights issues. Determines that non-smokers refuse to acknowledge the rights of those who choose to smoke. Refers to actions of a Mayor in St. Paul, who attempted to restrict smoking in buildings, city offices, and cars.